2017
DOI: 10.12944/crnfsj.5.3.13
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity and Total Phenolic Content of Fresh, Oven-Dried and Stir-Fried Tamarind Leaves

Abstract: The aim of this study was to compare the antioxidant capacity and total phenolic content as well as the chemical groups of fresh, oven-dried and stir-fried tamarind (Tamarindus indica L.) leaves. Methanol was used for extraction of fresh, oven-dried and stir-fried tamarind leaves. The stir-fried leaves were prepared using medium heat for 10 minutes prior to extraction and chemical analysis while dried leaves were obtained by oven drying at 60°C for 3 hours. The stir-fried leaves had significantly highest total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…It was believed that kenaf leaves extract prepared by oven drying improved the antioxidant properties. This result is in accordance with a previous study (Brozkova et al, 2016) which stated that oven drying of kenaf leaves can serve as a post-harvest storage method while improving the antioxidant activities (Mediani et al, 2014;Leng et al, 2017). A more recent study suggested that fresh kenaf leaves had the lowest value in the antioxidants activities test when compared to dried kenaf leaves (Sim and Nyam, 2019).…”
Section: Antioxidant Activities Of Kltsupporting
confidence: 91%
“…It was believed that kenaf leaves extract prepared by oven drying improved the antioxidant properties. This result is in accordance with a previous study (Brozkova et al, 2016) which stated that oven drying of kenaf leaves can serve as a post-harvest storage method while improving the antioxidant activities (Mediani et al, 2014;Leng et al, 2017). A more recent study suggested that fresh kenaf leaves had the lowest value in the antioxidants activities test when compared to dried kenaf leaves (Sim and Nyam, 2019).…”
Section: Antioxidant Activities Of Kltsupporting
confidence: 91%
“…Leng et al [ 27 ] compared the total content of phenolic compounds and the antioxidant capacity of fresh tamarind ( Tamarindus indica L.) leaves dried at 60 °C for 3 h or dried at 180 °C for 10 min. The total antioxidant capacity and total phenolic compound content in the extract were highest in the case of leaves dried at 180 °C.…”
Section: Drying the Plant Materialsmentioning
confidence: 99%
“…A standard curve was prepared by gallic acid at different concentrations to calculate the total phenol content. Total phenol was reported as mg gallic acid equivalents (GAE) L −1 [26].…”
Section: Total Phenolsmentioning
confidence: 99%